Integrating FIRO and AIDDA in Volunteer-Based Interpersonal Communication: A Socio-Spiritual Empowerment Model for Street Children - Ramadoni, Muhamad Afdoli; Ahmad Jumhan; Muhammad Zainuddin Nawi; Abu Hanifah; Titin Yenni; Ayu Munawwaroh (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2026)
Street children remain one of the major social problems in urban areas, particularly due to their limited access to education, social support, and psychological empowerment. Previous studies on street children have predominantly focused on social welfare, education, and government intervention, while paying limited attention to the role of interpersonal communication in volunteer-based community empowerment. This study aims to analyze how the South Sumatra Children's Volunteer Community (Relawan Anak Sumatera Selatan/RASS) practices interpersonal communication to empower street children in Palembang City. The novelty of this research lies in its application of the Fundamental Interpersonal Relationship Orientation (FIRO) theory to volunteer communication practices with marginalized children. This study employed a qualitative case study approach. Research was conducted at three locations: Baiturrahman Mosque, Jalan Kanan RT/RW 007/0014-5 Ulu Kertapati, Palembang; and the RASS Secretariat, located on Jalan Demang Lebar Daun, Ilir Barat I District, Palembang City. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that interpersonal communication established by RASS volunteers plays a significant role in fostering self-confidence, social belonging, and emotional attachment among street children. The communication process reflects the three dimensions of FIRO theory: inclusion, control, and affection. Volunteers encourage children to feel accepted within a supportive community, develop positive social interactions, and build emotional connectedness that strengthens their motivation and self-empowerment. This study contributes to the development of community communication studies by demonstrating that interpersonal communication can function not only as a medium of interaction but also as a transformative strategy for social empowerment among marginalized groups.